GEOCHEMICAL INVESTIGATION OF URBANISED TERRITORIES FOR NATURE PROTECTION (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 1999)
Complex geochemical investigations including topsoil, river sediments, water and sediments of dug wells that have been accomplished in Panevezys by Geochemistry department of the Institute of Geology are presented. The methods that were used are described and the main obtained results discussed.